A high-toughness TiCN-based cermet and preparation method thereof
By using TiC0.7N0.3, Co, Ni and (W, Ti, Ta, V, Mo)C solid solution, the high toughness and insufficient fracture toughness are solved, and the high toughness and flexural strength of the material are significantly improved.
Patent Information
- Application Number
- CN202411740222.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-04
AI Technical Summary
TiCN-based cermet has low flexural strength, low hardness and insufficient fracture toughness, which limits its application scale and scope.
TiC0.7N0.3, Co, Ni and (W, Ti, Ta, V, Mo)C solid solution as raw materials is used to prepare high-toughness TiCN-based metal cermets through ball milling, drying, pressing and degreasing sintering to form a ring-free structure and a weak core ring structure with a thin ring thickness to improve the toughness and bending strength of the material.
The fracture toughness and bending strength of TiCN-based cermets are significantly improved, and the comprehensive mechanical properties of the material are enhanced, making it less likely to break when it withstands of impact and stress.
Smart Images

Figure CN119753403A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal ceramic materials, in particular to a high-toughness TiCN-based metal ceramic and a preparation method thereof. Background Art
[0002] Ti(C,N)-based cermets use Ti(C,N) solid solution or (TiC+TiN) as hard phase, metal Ni, Co or their alloys as bonding phase, and other carbides (WC, Mo2C, TaC, NbC, etc.) as additives. Compared with conventional cemented carbide, Ti(C,N)-based cermets have higher hardness, and its wear resistance is 3 to 5 times that of commonly used cemented carbide. Cermets have higher red hardness, better high-temperature wear resistance and oxidation resistance. When used as a tool, it has excellent dry cutting performance and its cutting efficiency is 3 to 10 times higher than that of cemented carbide tools. In addition, Ti(C,N)-based cermets do not contain or only contain trace amounts of scarce strategic precious metals such as W and Co. The main raw materials Ti and Ni are widely available and inexpensive, so their manufacturing cost is only about 40% to 45% of that of cemented carbide. However, compared with cemented carbide, Ti(C,N)-based cermets still have the problems of large brittleness and insufficient toughness, which seriously limits their application scale and scope. Therefore, optimizing the performance of Ti(C,N)-based cermets and preparing cermets with high hardness and high toughness are of great significance to promoting the development of my country's processing manufacturing industry and the advancement of high-speed cutting technology, and it is one of the current research hotspots and focuses.
[0003] In order to improve the problem of insufficient toughness of TiCN-based cermets, various carbides such as Mo2C, WC, VC, Cr3C2, TaC, and NbC are usually added to improve the wettability of cermets, inhibit the growth of alloy grains, and improve high-temperature red hardness to improve the comprehensive mechanical properties of cermets. The second phase carbides (Mo2C, WC, VC, Cr3C2, TaC, and NbC) participate in the dissolution process during the sintering process to form a core ring structure to improve the wettability of the hard phase and the bonding phase, and improve the density and performance of the material. However, due to the addition of multiple components, complex metallurgical reactions are formed, resulting in uneven organization, structure, and composition of the annular phase, which reduces the mechanical properties of cermets. Although the toughness of cermets has been improved to a certain extent, under the condition of the same bonding phase content, there is still a big gap from the toughness of cemented carbide. Summary of the invention
[0004] The invention provides a high-toughness TiCN-based cermet and a preparation method thereof, which can solve the problems of low bending strength, low hardness and insufficient fracture toughness of the TiCN-based cermet.
[0005] This application provides the following technical solutions:
[0006] A method for preparing a high-toughness TiCN-based cermet comprises the following steps:
[0007] S1. Prepare raw materials, including TiC 0.7 N 0.3 , Co, Ni and (W, Ti, Ta, V, Mo) C solid solution, TiC 0.7 N 0.3 , Co, Ni and (W, Ti, Ta, V, Mo) C solid solution mass ratio is 20-70:4-15:5-15:20-50;
[0008] S2, ball milling the raw materials to obtain slurry;
[0009] S3, drying the slurry to obtain powder;
[0010] S4, pressing the powder to obtain a green body;
[0011] S5. Degreasing and sintering the green body to obtain high-strength and toughness TiCN-based cermets.
[0012] The invention discloses a high-toughness TiCN-based cermet prepared by a preparation method of a high-toughness TiCN-based cermet.
[0013] Beneficial Effects: TiC 0.7 N 0.3 As the main component, it provides high strength and hardness. Co and Ni are binders, which improve the toughness and plasticity of the material. (W, Ti, Ta, V, Mo) C is added in the form of solid solution, which can effectively reduce the dissolution-precipitation process during the sintering process, and finally form a ring-free structure and a weak core ring structure with a thin ring thickness, avoiding the ring phase from being too thick and reducing the toughness of the alloy, thereby significantly improving the toughness of the alloy. At the same time, compared with the traditional preparation method, due to the large number of carbide types, mechanical mixing is used, which is easy to produce segregation during the sintering process. The ball milling used in this technical solution makes the raw material components more evenly mixed, which is conducive to the mutual diffusion of the components during sintering, and the preparation method effectively avoids the occurrence of segregation. The metal ceramics prepared by this technical solution have higher fracture toughness and flexural strength, improve the toughness and plasticity of the metal ceramic material, and make it less likely to break when subjected to impact and stress.
[0014] Furthermore, the mass ratio of the raw material components of step S1-1 is as follows: the mass ratio of WC, Tic, TaC, VC and Mo2C is 20-25:1-2:8-10:0.5-1:10-15.
[0015] The addition of WC and Mo2C can improve the wettability between the ceramic phase and the bonding phase. The improvement of wettability increases the driving force for the formation of the ring core structure. The ring phase inhibits the aggregation and growth of the ceramic phase and improves the mechanical properties of the metal ceramic. TaC improves high-temperature performance. VC dissolves in the bonding phase, which improves the plasticity of the ring phase, enhances the bending strength, and improves the toughness of the material. The above mass ratio of WC, Tic, TaC, VC and Mo2C can improve the toughness, hardness, wear resistance and high-temperature performance of the material, so that it can show better performance in practical applications.
[0016] Furthermore, the preparation method of the (W, Ti, Ta, V, Mo)C solid solution comprises the following steps:
[0017] S1-1. Place W2O3, TiO, Ta2O5, V2O3, MoO3 and carbon black into a ball mill and perform high-energy ball milling to obtain a uniformly mixed powder.
[0018] S1-2. Place the uniformly mixed powder into a vacuum furnace and react at a temperature of 1400-1600° C. to obtain (W, Ti, Ta, V, Mo)C solid solution powder.
[0019] During ball milling, high-energy ball milling is used to prepare pre-solid carbides, so that the powders are mixed more evenly, which is conducive to the mutual diffusion of alloy elements during high-temperature reduction, ensuring the complete solid solution of the powders. At the same time, high-energy ball milling makes the powders more active, so that the carbon thermal reduction reaction is carried out at a very low temperature, thereby saving reaction costs and improving preparation efficiency. Ensure that the components of the obtained (W, Ti, Ta, V, Mo) C solid solution powder are evenly distributed in the microstructure.
[0020] Furthermore, the TiC 0.7 N 0.3 The particle size of is 1-1.5 μm, the particle size of Co is 1-2 μm, the particle size of Ni is 1-2 μm, and the particle size of (W, Ti, Ta, V, Mo)C solid solution powder is less than 1 μm.
[0021] Such particle size helps the components to mix more evenly during the ball milling process, thereby improving the uniformity and density of the final material.
[0022] Furthermore, during the ball milling in step S2, polyethylene glycol, carbide balls and 98% industrial alcohol are added, the mass ratio of carbide balls to the material to be ball milled is 10-15:1, the amount of alcohol added is 280-500 ml / kg, and the ball milling time is 24-72 h.
[0023] Carbide balls have high hardness and wear resistance, which can effectively grind and mix powder raw materials to ensure uniform distribution of each component. 98% industrial alcohol is used as ball milling medium to reduce friction between powders, prevent powder agglomeration, and improve mixing uniformity.
[0024] Furthermore, the drying in step S3 is performed by spray drying, and the average particle size of the obtained spray powder is 100 μm.
[0025] Beneficial effects: The powder with an average particle size of 100 μm has good fluidity, which helps to fill the mold more easily and reduce voids and unevenness in the subsequent pressing process.
[0026] Furthermore, the molding pressure of the press molding in step S4 is 100 MPa.
[0027] Beneficial effects: The molding pressure of 100MPa can ensure the compaction density of the powder, thereby ensuring the density and mechanical properties of the metal ceramic material.
[0028] Furthermore, the debinding sintering in step S5 adopts a low-pressure sintering furnace. During the sintering process, when the temperature is 1200°C, it is kept warm for 30 to 40 minutes; when the temperature is 1300°C, it is kept warm for 30 to 40 minutes; when the temperature is increased from 1300°C to 1480 to 1500°C, 500 to 2000 Pa of nitrogen is filled during the firing period to perform partial pressure sintering; when the temperature is 1480 to 1500°C, it is kept warm for 30 to 45 minutes, and vacuum is drawn during the holding period to perform vacuum sintering; the temperature is continued to be kept at 1480 to 1500°C for 15 to 30 minutes, and argon is slowly filled to 2 MPa; after continuing to keep warm at 1480 to 1500°C for 30 to 45 minutes, a rapid cooling treatment is performed to obtain a high-strength and tough TiCN-based metal ceramic.
[0029] During the sintering process, nitrogen partial pressure is used to maintain the nitrogen balance of the alloy system and the sintering atmosphere, avoid alloy denitrification, and inhibit the dissolution of alloy elements into the binder phase. Therefore, more Ti (C, N) particles are retained, the microstructure of the material is refined, and the volatilization of nitrogen from the sample at high temperature can be reduced, thereby reducing the residual pores.
[0030] Furthermore, in the rapid cooling treatment, argon gas is quickly injected to 1-6 MPa, the temperature is reduced to 1350° C. within 10 minutes, and then the temperature is naturally cooled.
[0031] Beneficial effects: Rapid cooling can effectively reduce the dissolution and precipitation process during the cooling process, reduce the precipitation of elements on the core phase, maintain the temperature of the TiCN core-ring structure, and obtain a moderately thick and complete ring phase. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1This is a metallographic photograph of a high-toughness TiCN-based cermet of the present invention.
[0033] Figure 2 This is a Vickers hardness load indentation diagram of a high-toughness TiCN-based cermet of the present invention.
[0034] Figure 3 This is a scanning electron microscope photograph of a high-toughness TiCN-based cermet of the present invention. DETAILED DESCRIPTION
[0035] The following is further described in detail through specific implementation methods:
[0036] Embodiment 1
[0037] A method for preparing a high-toughness TiCN-based cermet comprises the following steps:
[0038] S1. Prepare raw materials, including TiC 0.7 N 0.3 , Co, Ni and (W, Ti, Ta, V, Mo) C solid solution, TiC 0.7 N 0.3 The mass ratio of WC, TiC, TaC, VC and Mo2C in the (W, Ti, Ta, V, Mo)C solid solution is 24:1:10:0.6:13.4. 0.7 N 0.3 The particle size of is 1.2 μm, the particle size of Ni is 1.5 μm, the particle size of Co is 1.5 μm, and the particle size of the (W, Ti, Ta, V, Mo) C solid solution powder is 0.6 μm.
[0039] The preparation method of the (W, Ti, Ta, V, Mo)C solid solution comprises the following steps:
[0040] S1-1, put the raw materials W2O3, TiO, Ta2O5, V2O3, MoO3 and carbon black into a stainless steel ball mill, use carbide balls, no ball milling medium, and perform high-energy ball milling to obtain a uniformly mixed powder. The mass ratio of the carbide balls to the total amount of the raw materials to be ball milled is 10:1; the speed of the planetary ball mill is 1200r / min, and the ball milling time is 0.5 to 2 hours.
[0041] S1-2. Place the uniformly mixed powder into a tubular vacuum furnace and react at a temperature of 1400-1600°C to obtain a (W, Ti, Ta, V, Mo)C solid solution powder. The mass ratio of WC, Tic, TaC, VC and Mo2C in the (W, Ti, Ta, V, Mo)C solid solution powder is 24:1:10:0.6:13.4.
[0042] S2, prepare the powdered TiC 0.7 N 0.3 , Co, Ni, (W, Ti, Ta, V, Mo)C solid solution and polyethylene glycol-4000 (PEG 4000) are put into a nylon ball mill, the amount of PEG 4000 added is 1.5% of the total amount of raw materials, and cemented carbide balls and 98% industrial alcohol are added for ball milling. The mass ratio of cemented carbide balls to the material to be ball milled is 10:1, the amount of alcohol added is 280-500 ml / kg, the speed of the ball mill is 200-500 r / min, the speed of the ball mill in this embodiment is 272 r / min, and the ball milling time is 24-72 h to obtain a ball-milled slurry.
[0043] S3. Using a spray dryer, spray-dry the slurry obtained in step S2 to obtain a spray powder with an average particle size of 100 μm.
[0044] S4, putting the spray powder obtained in step S3 into a press to form a green body, with a forming pressure of 100 MPa.
[0045] S5. Put the green body obtained in step S4 into a low-pressure sintering furnace for degreasing and sintering at a sintering temperature of 1480-1500° C. to obtain a high-strength and tough TiCN-based cermet.
[0046] The specific steps of sintering are as follows:
[0047] After 58 minutes of firing, the sintering temperature was raised from room temperature to 150°C. After 2 hours of firing, the temperature was raised from 150°C to 260°C, and kept at 260°C for 40 minutes. During the firing and keeping temperature period, 800Pa of flowing argon was injected. After 3 to 3.5 hours of firing, the temperature was raised from 260°C to 550°C, and kept at 550°C for 40 minutes. During the firing and keeping temperature period, 800Pa of flowing argon was injected. Continue firing for 21 minutes, raise the temperature from 550℃ to 650℃, and keep it at 650℃ for 30 minutes; continue firing for 60-95 minutes, raise the temperature from 650℃ to 1070℃, and keep it at 1070℃ for 60 minutes; continue firing for 40 minutes, raise the temperature from 1070℃ to 1200℃, and keep it at 1200℃ for 30 minutes; continue firing for 32 minutes, raise the temperature from 1200℃ to 1300℃, and keep it at 1300℃ for 30 minutes. Continue firing for 50-60 minutes, raise the temperature from 1300℃ to 1480℃, and inject 600-800Pa of nitrogen during firing to perform partial pressure sintering. Keep it at 1480℃ for 45 minutes, and evacuate during the insulation period to perform vacuum sintering. Keep it at 1480℃ for 15 minutes, and slowly inject argon to 2MPa. After keeping the temperature at 1480°C for 45 min, argon gas was quickly injected to 6 MPa, and the temperature was reduced to 1350°C within 10 min. Then, the temperature was naturally cooled to obtain a finished high-strength and tough TiCN-based cermet. The finished product properties are shown in Table 1.
[0048] Embodiment 2
[0049] A method for preparing a high-toughness TiCN-based cermet comprises the following steps:
[0050] S1. Prepare raw materials, including TiC 0.7 N 0.3 , Co, Ni and (W, Ti, Ta, V, Mo) C solid solution, TiC 0.7 N 0.3 The mass ratio of WC, TiC, TaC, VC, and Mo2C in the (W, Ti, Ta, V, Mo)C solid solution is 25:1:8:0.5:10.5. 0.7 N 0.3 The particle size of is 1.2 μm, the particle size of Ni is 1.5 μm, the particle size of Co is 1.5 μm, and the particle size of the (W, Ti, Ta, V, Mo) C solid solution powder is 0.6 μm.
[0051] The preparation method of the (W, Ti, Ta, V, Mo)C solid solution comprises the following steps:
[0052] S1-1, put the raw materials W2O3, TiO, Ta2O5, V2O3, MoO3 and carbon black into a stainless steel ball mill, use carbide balls, no ball milling medium, and perform high-energy ball milling to obtain a uniformly mixed powder. The mass ratio of the carbide balls to the total amount of the raw materials to be ball milled is 10:1; the speed of the planetary ball mill is 1200r / min, and the ball milling time is 0.5 to 2 hours.
[0053] S1-2. Place the uniformly mixed powder into a tubular vacuum furnace and react at a temperature of 1400-1600°C to obtain a (W, Ti, Ta, V, Mo)C solid solution powder. The mass ratio of WC, Tic, TaC, VC, and Mo2C in the (W, Ti, Ta, V, Mo)C solid solution powder is 25:1:8:0.5:10.5.
[0054] S2, prepare the powdered TiC 0.7 N 0.3 , Co, Ni, (W, Ti, Ta, V, Mo)C solid solution and polyethylene glycol-4000 (PEG 4000) are put into a nylon ball mill, the amount of PEG 4000 added is 1.5% of the total amount of raw materials, carbide balls and 98% industrial alcohol are added for ball milling, the mass ratio of carbide balls to the material to be ball milled is 10:1, the amount of alcohol added is 280-500 ml / kg, the ball milling time is 24-72 h, the speed of the ball mill is 200-500 r / min, and the speed of the ball mill in this embodiment is 270 r / min to obtain a ball-milled slurry.
[0055] S3. Using a spray dryer, spray-dry the slurry obtained in step S2 to obtain a spray powder with an average particle size of 100 μm.
[0056] S4, putting the spray powder obtained in step S3 into a press to form a green body, and the forming pressure is 100 MPa.
[0057] S5. Put the green body obtained in step S4 into a low-pressure sintering furnace for degreasing and sintering at a sintering temperature of 1480-1500° C. to obtain a high-strength and tough TiCN-based cermet.
[0058] The specific steps of sintering are as follows:
[0059] After 58 minutes of firing, the sintering temperature was raised from room temperature to 150°C. After 2 hours of firing, the temperature was raised from 150°C to 260°C, and kept at 260°C for 40 minutes. During the firing and keeping temperature period, 800Pa of flowing argon was injected. After 3 to 3.5 hours of firing, the temperature was raised from 260°C to 550°C, and kept at 550°C for 40 minutes. During the firing and keeping temperature period, 800Pa of flowing argon was injected. Continue firing for 21 minutes, raise the temperature from 550℃ to 650℃, and keep it at 650℃ for 30 minutes; continue firing for 60-95 minutes, raise the temperature from 650℃ to 1070℃, and keep it at 1070℃ for 60 minutes; continue firing for 40 minutes, raise the temperature from 1070℃ to 1200℃, and keep it at 1200℃ for 30 minutes; continue firing for 32 minutes, raise the temperature from 1200℃ to 1300℃, and keep it at 1300℃ for 30 minutes. Continue firing for 50-60 minutes, raise the temperature from 1300℃ to 1500℃, and inject 600-800Pa of nitrogen during firing to perform partial pressure sintering. Keep it at 1500℃ for 45 minutes, and evacuate during the insulation period to perform vacuum sintering. Keep it at 1500℃ for 15 minutes, and slowly inject argon to 2MPa. After keeping the temperature at 1500°C for 45 minutes, argon gas was quickly injected to 4-6 MPa, and the temperature was reduced to 1350°C within 10 minutes. Then, the temperature was naturally cooled to obtain a finished high-strength and tough TiCN-based cermet. The finished product properties are shown in Table 1.
[0060] Comparative Example 1
[0061] The difference between Comparative Example 1 and Example 1 is that no (W, Ti, Ta, V, Mo)C solid solution is prepared, and WC, Tic, TaC, VC, and Mo2C are directly added. The mass percentage of each component of the raw material is: TiC 0.7 N 0.3 : 41%, Co: 4%, Ni: 11%, WC: 25%, Mo2C: 10.5%, TaC: 8%, VC0.5%. The prepared raw materials were ball milled, dried, pressed, sintered to obtain the finished product, which was tested and the properties of the finished product are shown in Table 1.
[0062] Comparative Example 2
[0063] The difference between the comparative example 2 and the embodiment 1 is that the specific steps of sintering are different, nitrogen is not injected for partial pressure sintering, and rapid cooling treatment is not performed. When the comparative example 2 is sintered, the specific steps include: the temperature is increased from 1070°C to 1200°C and then kept warm for 30 minutes; continue firing, increase the temperature from 1200°C to 1300°C and then keep warm for 30 minutes; continue firing, increase the temperature from 1300°C to 1440°C, keep warm at 1440°C for 60 minutes, quickly inject 4MPa argon, cool down to below 800°C within 1 hour, cool, and the performance of the finished product is shown in Table 1 below.
[0064] Table 1
[0065]
[0066] As can be seen from Table 1, the TiCN-based metal ceramic materials prepared in Example 1 and Example 2 have higher hardness and bending strength than the finished products prepared in Comparative Example 1 and Comparative Example 2, and improve the fracture toughness of the metal ceramic materials. After the TiCN-based metal ceramic materials prepared in Example 1 and Example 2 are made into cutting tools, they are not easy to break when subjected to impact and stress. After multiple tests on the cutting tools, it is found that the number of workpieces that can be processed by the cutting tools made of the finished product of Example 1 is between 6000 and 8600 pieces, and the number of workpieces that can be processed by the cutting tools made of the finished product of Example 2 is between 6300 and 8800 pieces; the number of workpieces that can be processed is much greater than the number of workpieces that can be processed by the cutting tools made of the finished products of Comparative Example 1 and Comparative Example 2.
[0067] The above are only embodiments of the present invention. The invention is not limited to the field involved in this implementation case. The common knowledge such as the known specific structure and characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the structure of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing a high-toughness TiCN-based cermet, characterized in that: The steps include: S1. Prepare raw materials, including TiC 0.7 N 0.3 , Co, Ni and (W, Ti, Ta, V, Mo) C solid solution, TiC 0.7 N 0.3 , Co, Ni and (W, Ti, Ta, V, Mo) C solid solution mass ratio is 20-70:4-15:5-15:20-50; S2, ball milling the raw materials to obtain slurry; S3, drying the slurry to obtain powder; S4, pressing the powder to obtain a green body; S5. Degreasing and sintering the green body to obtain high-strength and toughness TiCN-based cermets.
2. The method according to claim 1, characterized in that: The mass ratio of WC, Tic, TaC, VC and Mo2C in the (W, Ti, Ta, V, Mo)C solid solution is 20-25:1-2:8-10:0.5-1:10-15.
3. The method according to claim 1, characterized in that: The preparation method of the (W, Ti, Ta, V, Mo) C solid solution comprises the following steps: S1-1, W2O3, TiO, Ta2O5, V2O3, MoO3 and carbon black are placed in a ball mill and subjected to high-energy ball milling to obtain a uniformly mixed powder; S1-2. Place the uniformly mixed powder into a vacuum furnace and react at a temperature of 1400-1600° C. to obtain (W, Ti, Ta, V, Mo)C solid solution powder.
4. The method according to claim 1, characterized in that: The TiC 0.7 N 0.3 The particle size of is 1-1.5μm, the particle size of Co is 1-2μm, the particle size of Ni is 1-2μm, and the particle size of (W, Ti, Ta, V, Mo)C solid solution is less than 1μm.
5. The method according to claim 1, characterized in that: When ball milling is performed in step S2, polyethylene glycol, carbide balls and 98% industrial alcohol are added, the mass ratio of carbide balls to the material to be ball milled is 10-15:1, the amount of alcohol added is 280-500 ml / kg, and the ball milling time is 24-72 hours.
6. The method according to claim 1, characterized in that: The drying in step S3 is carried out by spray drying, and the average particle size of the obtained powder is 100 μm.
7. The method according to claim 1, characterized in that: The molding pressure of the press molding in step S4 is 100 MPa.
8. The method according to claim 1, characterized in that: The debinding sintering in step S5 adopts a low-pressure sintering furnace. During the sintering process, when the temperature is 1200°C, it is kept warm for 30 to 40 minutes; when the temperature is 1300°C, it is kept warm for 30 to 40 minutes; when the temperature is increased from 1300°C to 1480 to 1500°C, 500 to 2000Pa of nitrogen is filled during the firing period to perform partial pressure sintering; when the temperature is 1480 to 1500°C, it is kept warm for 30 to 45 minutes, and vacuum is drawn during the holding period to perform vacuum sintering; the temperature is continued to be kept at 1480 to 1500°C for 15 to 30 minutes, and argon is slowly filled to 2MPa; after continuing to keep warm at 1480 to 1500°C for 30 to 45 minutes, a rapid cooling treatment is performed to obtain a high-strength and tough TiCN-based metal ceramic.
9. The method according to claim 8, characterized in that: The rapid cooling treatment includes rapidly injecting argon gas to a pressure of 1-6 MPa, reducing the temperature to 1350° C. within 10 minutes, and then cooling naturally.
10. A high-toughness TiCN-based cermet prepared by the method of any one of claims 1 to 9.